Information literacy: an essential pillar of digital citizenship / Syaiful Hisyam Saleh and Noor Shahariah Saleh - Saleh, Syaiful Hisyam; Saleh, Noor Shahariah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In the contemporary period characterised by swift technological progress, acquiring information literacy has assumed paramount importance, as it fosters the notion of digital citizenship. In light of the ongoing influence of technology on communication, information acquisition, and societal engagement, it is crucial to conscientiously and ethically traverse the extensive realm of available information. Information literacy plays a key role in enabling individuals to assume the role of responsible digital citizens, fostering a beneficial influence on society. Fundamentally, information literacy involves the capacity to proficiently access, assess, and employ information in a purposeful manner. In addition to critical analysis, evaluation of source reliability, and recognition of potential biases, the process extends beyond just online information retrieval. By cultivating information literacy abilities, individuals acquire the essential resources to engage in informed decision-making, actively participate in online discourse, and make valuable contributions to the digital realm.